RANCANG BANGUN TURNING ATTACHMENT UNTUK PROSES DUPLIKAT BENDA KERJA PADA MESIN BUBUT KONVENSIONAL - M. Wildan Al Fanany; Bayu Wiro Karuniawan; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
One of the efforts to increase productivity is skillful and competent human resources, Surabaya State Marine Polytechnic as one of the Higher Education Institutions, has implemented the Teaching Factory Learning model, with this method the campus could do an cooperation with companies to make commercial products, in order to support Teaching factory, an innovation in conventional lathes is needed to duplicate and produce large quantities of manufactured product, therefore it is necessary to make a Turning Attachment for duplicating workpieces on conventional lathes. From those problem leads to an invention and investigation regarding the design, manufacturing process, cost of production, strength analysis, and working method of the Turning Attachment. In this study, the Ulrich method was used with the output of a tool that could perform duplication process that produced the desired shape. The results of the trial shows that this tool can duplicate the workpiece according to the mall with an angle below 39º, with acceptable tolerance of 0.1. The total production cost budget for the Turning Attachment is Rp. 3,144,000.00.